2018
DOI: 10.1038/s41467-018-04254-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid pathway prototyping and engineering using in vitro and in vivo synthetic genome SCRaMbLE-in methods

Abstract: Exogenous pathway optimization and chassis engineering are two crucial methods for heterologous pathway expression. The two methods are normally carried out step-wise and in a trial-and-error manner. Here we report a recombinase-based combinatorial method (termed “SCRaMbLE-in”) to tackle both challenges simultaneously. SCRaMbLE-in includes an in vitro recombinase toolkit to rapidly prototype and diversify gene expression at the pathway level and an in vivo genome reshuffling system to integrate assembled pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 57 publications
2
77
0
1
Order By: Relevance
“…Our efforts demonstrated that V. natriegens heterologously produced violacein (and deoxyviolacein) in both rich media and in minimal media containing the six carbon sources tested. In rich medium, the production of violacein with V. natriegens (~13 mg·L −1 ) was similar to the production observed in E. coli (~15 mg·L −1 ) when using a plasmid containing the same RBS as pVio [21], although higher production has been demonstrated in other optimized systems [23,25,69,70]. Interestingly, production was high when grown in mannitol or glycerol.…”
Section: Heterologous Production Of Violaceinsupporting
confidence: 74%
“…Our efforts demonstrated that V. natriegens heterologously produced violacein (and deoxyviolacein) in both rich media and in minimal media containing the six carbon sources tested. In rich medium, the production of violacein with V. natriegens (~13 mg·L −1 ) was similar to the production observed in E. coli (~15 mg·L −1 ) when using a plasmid containing the same RBS as pVio [21], although higher production has been demonstrated in other optimized systems [23,25,69,70]. Interestingly, production was high when grown in mannitol or glycerol.…”
Section: Heterologous Production Of Violaceinsupporting
confidence: 74%
“…Synthetic biology approaches can also be used to engineer strains for improved yield and productivity; it provides an opportunity to engineer biology in a more standardized and rational fashion, and several examples using a synthetic yeast genome have been described (Liu et al 2018). One of these approaches is the rewiring of metabolic flux by deleting genes that negatively affect enzyme production.…”
Section: Automated Strain Construction Systems Biology and Synthetimentioning
confidence: 99%
“…By enabling controllable chromosome rearrangements between the designed loxP sites, a synthetic yeast can delete, duplicate and reorder many of its genes, allowing in vivo selection for desirable traits such as increased alkali tolerance [62]. Alternatively, the system can be coupled to heterologously expressed genes allowing the rapid optimisation of pathways [63].…”
Section: Second-generation Tools and Applicationsmentioning
confidence: 99%